The Philippine environment - Philippines. Environmental Management Bureau. Environmental Education and Information Division ([S.l.] Megascope Graphics)
Shows the Philippine ecosystem including land, coast and fresh water. These rich natural resources are endangered by pollution.
VHS
Keywords: Natural resources -- Philippines; Environmental health -- Philippines; Pollutants -- Philippines; Environmental science